Pembaharuan Pendidikan Islam Perspektif Hamka - Adi Sulistyo Wibowo; Ahmad Fathir Qodri; Sudarto Sudarto; M. Effendi; Mulyanto Abdullah Khoir (Jurnal Budi Pekerti Agama Islam, 2024)
Buya Hamka is an Indonesian scholar who has an earthly thinking and a vision of the future, many works and fruits of Hamka's thoughts that color the world, especially Islam. Hamka's involvement in various aspects of science shows that he is an intelligent, inspiring figure and there are many other things that we can adopt to impress future generations like Hamka. Thus, the prophet Muhammad (peace and blessings be upon him) revealed to the people that he is the God of all things. There have been 118 works by Buya Hamka since 1925.